Effect of footplate neuromuscular electrical stimulation on functional and quality-of-life parameters in patients with peripheral artery disease: pilot, and subsequent randomized clinical trial. Issue 4 (7th January 2020) - Babber, A; Ravikumar, R; Onida, S; Lane, T R A; Davies, A H
Abstract: Background: Supervised exercise programmes for intermittent claudication have poor access and limited compliance. Neuromuscular electrical stimulation (NMES) may be an effective alternative. A proof-of-concept study and RCT were conducted. Methods: In study 1, eligible patients underwent baseline assessment; treadmill testing for initial (ICD) and maximum (MCD) claudication distance; EuroQoL Five Dimensions five-level instrument (EQ-5D-5L™) and Intermittent Claudication Questionnaire (ICQ) assessment; and measurement of ultrasound haemodynamics of the superficial femoral artery. After familiarization with the NMES device, participants underwent a 30-min session of stimulation with concomitant recording of haemodynamic measures at 15 min, and after device cessation. Measurements were repeated after 6 weeks of daily use of NMES. In study 2, consecutive patients underwent baseline assessment before online randomization to a supervised exercise programme only, or adjunctive NMES treatment for 6 weeks, followed by repeat measurements. Results: Study 1 (20 patients) showed a significant improvement in MCD (46 per cent; P < 0·001) and ICD (71 per cent; P < 0·001). The RCT (42 patients) showed a significant adjunctive benefit of NMES in ICD (46 per cent; P = 0·014). Improvements were seen in the ICQ (9 points; P = 0·009) and EQ-5D-5L™ ( P = 0·007) in study 1, and there was a significant adjunctive benefit of NMES on the ICQ score in patients who did supervised exercise (11·2 points; P = 0·031). Blood volume flow and time-adjusted mean velocity increased significantly with the device on ( P < 0·050). Overall, NMES compliance exceeded 95 per cent. Conclusion: Footplate NMES significantly improved walking distance in patients with intermittent claudication when used independently and also as an adjunct to supervised exercise. Registration number: trial 1, NCT02436200; trial 2, NCT02429310 (http://www.clinicaltrials.gov ). Graphical Abstract: This article reports a pilot study and subsequent RCT assessing the value of a footplate neuromuscular electrical device in the management of patients with peripheral artery disease. This technology provided both functional and quality-of-life improvements in patients with intermittent claudication. Promising technology